2021
DOI: 10.3390/ijerph18179326
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Mood States during the Different Phases of COVID-19’s Lockdown in Young Athletes

Abstract: The pandemic caused by SARS-CoV-2 led to a situation of home lockdown. Competitions, training, and sports activities were canceled for much of this period. This situation could have affected the physical and mental health and the mood states of young athletes. The aim of the study was to evaluate the variations in the mood states of young athletes of a highly competitive level during the different phases of lockdown in. The mood states of 45 Spanish youth athletes confined during the 10-week lockdown due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…These results are in line with previous research that shows heightened anxiety both among healthy persons and individuals with pre-existing mental health problems during COVID-19 [ 35 ]. In addition, the results support previous research that found reductions in mental health and life satisfaction during confinements period of the pandemic among elite athletes and young athletes [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are in line with previous research that shows heightened anxiety both among healthy persons and individuals with pre-existing mental health problems during COVID-19 [ 35 ]. In addition, the results support previous research that found reductions in mental health and life satisfaction during confinements period of the pandemic among elite athletes and young athletes [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 89%
“…Although studies indicate that physical activity is a protective factor for mental health in the general population, an important question is if persons who are highly active on a regular basis are not prone to emotional consequences during the COVID-19 pandemic due to the protective effect of physical activity, or if also these individuals may suffer negative emotional effects. There is evidence to suggest that mental health was negatively affected during home confinement among elite athletes [ 25 ] and young athletes [ 26 ]. These findings suggest that even persons who have high levels of physical activity may experience negative emotional reactions during the pandemic situation.…”
Section: Introductionmentioning
confidence: 99%
“…Collective evidence from Europe (13,(55)(56)(57)(58)(59)(60)(61)(62)(63), Asia (64,65), Canada (66), South America (67), and the Middle East (68)(69)(70) is demonstrating that the pandemic-related restrictions had clear negative impact on mental well-being among athletes across all ages. Surveys administered one to three times during the pandemic have identified mood disturbances, behavioral changes, and varying levels of stress among competitors ranging in age from youth, collegiate through professional.…”
Section: Mental Health Impact Of Covid On Athletesmentioning
confidence: 99%
“…A patient in quarantine must meet all of the following criteria to be discharged:Symptomatic patients10 days after the onset of symptoms and 72 hours after the symptoms have abatedNegative results confirmed by two PCR tests at an interval of at least 24 hours, after 24 hours of symptom relief Asymptomatic pathogen retainersAfter 10 days from the date of specimen collectionAfter 6 days from the date of specimen collection, confirmed negative results of two PCR tests at an interval of at least 24 hours. Although previous studies have demonstrated that the lockdown affected the mental health of athletes, such as depressive mood and confusion [5], anxiety [6], and elevated distress [7], to our knowledge, no studies have reported psychiatric disorders caused by individual isolation during quarantine. Nevertheless, it is not contradictory that isolated athletes or associates were restricted freedom of action, including training, as well as tremendously distressed as they were deprived of the opportunity to participate in the main competition.…”
Section: Services For People Under Quarantinementioning
confidence: 65%
“…Although previous studies have demonstrated that the lockdown affected the mental health of athletes, such as depressive mood and confusion [5], anxiety [6], and elevated distress [7], to our knowledge, no studies have reported psychiatric disorders caused by individual isolation during quarantine. Nevertheless, it is not contradictory that isolated athletes or associates were restricted freedom of action, including training, as well as tremendously distressed as they were deprived of the opportunity to participate in the main competition.…”
Section: Services For People Under Quarantinementioning
confidence: 85%